2017
DOI: 10.1038/s41467-017-02114-x
|View full text |Cite
|
Sign up to set email alerts
|

ATM and CDK2 control chromatin remodeler CSB to inhibit RIF1 in DSB repair pathway choice

Abstract: CSB, a member of the SWI2/SNF2 superfamily, is implicated in DNA double-strand break (DSB) repair. However, how it regulates this repair process is poorly understood. Here we uncover that CSB interacts via its newly identified winged helix domain with RIF1, an effector of 53BP1, and that this interaction mediates CSB recruitment to DSBs in S phase. At DSBs, CSB remodels chromatin by evicting histones, which limits RIF1 and its effector MAD2L2 but promotes BRCA1 accumulation. The chromatin remodeling activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 63 publications
4
99
0
Order By: Relevance
“…We observed that, despite the relative increase in H2AK119Ub1 levels ( Figure 3A–C ), H2A levels were significantly reduced at the FokI nuclease-induced DNA damage sites ( Figure 6—figure supplement 1A ), in agreement with previous reports ( Batenburg et al, 2017 ; Berkovich et al, 2007 ; Strickfaden et al, 2016 ). Importantly, this reduction was inhibited by the depletion of FBXL10, RNF68, or RNF2, suggesting that the FRRUC is involved in the eviction of H2A near DNA damage sites ( Figure 6—figure supplement 1A ).…”
Section: Resultssupporting
confidence: 93%
“…We observed that, despite the relative increase in H2AK119Ub1 levels ( Figure 3A–C ), H2A levels were significantly reduced at the FokI nuclease-induced DNA damage sites ( Figure 6—figure supplement 1A ), in agreement with previous reports ( Batenburg et al, 2017 ; Berkovich et al, 2007 ; Strickfaden et al, 2016 ). Importantly, this reduction was inhibited by the depletion of FBXL10, RNF68, or RNF2, suggesting that the FRRUC is involved in the eviction of H2A near DNA damage sites ( Figure 6—figure supplement 1A ).…”
Section: Resultssupporting
confidence: 93%
“…When the paper was under revision, the study by Batenburg et al , showing that ATM and CDK2 control the chromatin remodeling activity of CSB in the regulation of DSB repair pathway choice, was published in Nature Communications [ 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…56 Additionally, as a member of the SWI2/ SNF2 superfamily, CBS could be phosphorylated by ATM and CDK2, which may regulate CBS chromatin remodeling activity involved in the DNA double-strand break (DSB) repair pathway. 57 Furthermore, the acetyltransferase PCAF could acetylate mammalian BRM to negatively impact BRM activities as a chromatin remodeler, including transcriptional activation as well as growth modulation. 58 However, the methylation of chromatin remodelers alone has been infrequently reported, especially arginine methylation.…”
Section: Discussionmentioning
confidence: 99%